2023
DOI: 10.3390/jcm12103369
|View full text |Cite
|
Sign up to set email alerts
|

COPD Exacerbation: Why It Is Important to Avoid ICU Admission

Abstract: Chronic obstructive pulmonary disease (COPD) is one of the major causes of morbidity and mortality worldwide. Hospitalization due to acute exacerbations of COPD (AECOPD) is a relevant health problem both for its impact on disease outcomes and on health system resources. Severe AECOPD causing acute respiratory failure (ARF) often requires admission to an intensive care unit (ICU) with endotracheal intubation and invasive mechanical ventilation. AECOPD also acts as comorbidity in critically ill patients; this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 115 publications
0
8
0
2
Order By: Relevance
“…Overall, 91 patients had a median time [IQR] of COPD diagnosis until hospital admission of 4 [ 2 , 3 , 4 , 5 , 6 ] years. Most of these patients (86.8%) had “more breathlessness”, as indicated by a mMRC score ≥2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 91 patients had a median time [IQR] of COPD diagnosis until hospital admission of 4 [ 2 , 3 , 4 , 5 , 6 ] years. Most of these patients (86.8%) had “more breathlessness”, as indicated by a mMRC score ≥2.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) is a heterogeneous respiratory disease that manifests various clinical presentations, including chronic dyspnea, cough, sputum production, and recurrent exacerbations [ 1 , 2 ]. It is typically associated with airway abnormalities (e.g., bronchiolitis) and alveolar destruction, leading to persistent and progressive worsening airflow limitation [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, individuals with severe disease often experience rapid deterioration and require hospitalization [ 5 ]. AECOPD is one of the most common causes of hospital admission, and those with frequent aggravation experience reduced quality of life and an accelerated decline in lung function [ 6 ]. Respiratory failure (RF) is a complication that contributes the most to the high mortality and poor prognosis of patients with AECOPD [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 It has been shown that patients with COPD hospitalized for AEs have a mortality rate of 25% and 65% at one year and five years, respectively. 11 Approximately 2%-19% of hospitalized AECOPD patients are ultimately transferred to the Intensive Care Unit (ICU), [12][13][14][15] and the ultimate in-hospital mortality rate for such patients is 12-24%, [16][17][18] with 35% of surviving patients expected to be readmitted to the hospital 3 months after discharge. 19,20 Owing to various factors, such as the large population of people with COPD in China and their widespread distribution, limited awareness of the disease among most patients, and unstandardized diagnosis and treatment of COPD primary medical care, most patients are unable to recognize AE at an early stage and cannot receive timely and effective standardized treatment and management.…”
Section: Introductionmentioning
confidence: 99%